THE IMPACT OF DIGITAL TECHNOLOGIES ON THE DEVELOPMENT OF NATIONAL ECONOMIES IN CENTRAL ASIA - Dustova Khudayberdievna, Mukhayyo (THE INNOVATION ECONOMY, 2025)
This article explores the impact of digitalization on the economies of Central Asian countries. Key areas of digital transformation are analyzed, including the development of e-commerce, digital infrastructure, financial inclusion, and automation. Particular attention is paid to challenges such as digital inequality, lack of digital literacy, and cybersecurity threats. Successful digital initiatives in Kazakhstan, Uzbekistan, and other countries in the region are highlighted. Recommendations are provided for the sustainable growth of the digital economy.